Environmental Archaeology: Meaning and Purpose - Albarella, Umberto (Environmental Science and Technology Library, 2001)
Despite the fact that the human life of the past cannot be understood without taking into account its ecological relationships, environmental studies are often marginalised in archaeology. This is the first book that, by discussing the meaning and purpose we give to the expression 'environmental archaeology', investigates the reasons for such a problem. This is achieved through the use of theoretical considerations and the aid of a number of case studies, which, by taking us from Anglo-Saxon England to pre-Columbian Venezuela, and from Classical Greece to late Antique Egypt, emphasise the potential of an integrated approach. The book is written by archaeologists with different backgrounds and is addressed to all researchers who care about the past relationship between people and the rest of Nature. Despite the complexity of some of the issues tackled, the book is written in an accessible manner and should be of interest to all students who want to understand the essence of archaeology beyond the boundary of the individual sub-disciplines